Socially Responsible Investment: How Far has been Researched? - Muhammad Syafii (SMART Insight, 2021)
Socially responsible investment become a topic that has been studied more and more in the last few decades. This study aims to analyze the literature related to socially responsible investment with coverage of research trends and future research directions. A total of 1,217 articles sourced from Scopus which were analyzed using the biblioshiny R software. The findings in this study include keywords that are often used in research, including socially responsible investment, mutual funds, socially responsible investing, and corporate social responsibility. While the authors who have the greatest contribution to this study are Scholtenz B, Peres-gladish, and Nilsson J. Finally, the latest topic trends in related research socially responsible investment are Covid-19, pandemic, ESG, and ratings.